Threshold energy

From Wikipedia, the free encyclopedia
Jump to: navigation, search

In particle physics, the threshold energy for production of a particle is the minimum kinetic energy a pair of traveling particles must have when they collide. The threshold energy is always greater than or equal to the rest energy of the desired particle. In most cases, since momentum is also conserved, the threshold energy is significantly greater than the rest energy of the desired particle - and thus there will still be considerable kinetic energy in the final particles.

Example[edit]

Look at the reaction of a proton hitting a stationary proton,  p + p \to p + p + \pi^0.

By going into the center of mass frame, and assuming the outgoing particles have no kinetic energy the conservation of energy equation is:

 E = 2\gamma m_pc^2 = 2 m_pc^2+ m_\pi c^2

 \gamma = \frac{1}{\sqrt{1-\beta^2}} = \frac{2 m_pc^2+ m_\pi c^2}{2 m_pc^2}

 \beta^2 = 1-(\frac{2 m_pc^2}{2 m_pc^2+ m_\pi c^2})^2 \approx 0.13

Using relativistic velocity additions:

 v_\text{lab} = \frac{u_\text{cm} + v_\text{cm}}{1+u_\text{cm}v_\text{cm}/c^2} \approx 0.64 c

So the energy of the proton must be  E = \gamma m_p c^2 = \frac{m_p c^2}{\sqrt{1-\beta^2}} = 1221\,MeV.

A more general example[edit]

Let's look at the case where a particle 1 with lab energy E_1 (momentum p_1) and mass m_1 impinges on a target particle 2 at rest in the lab, i.e. with lab energy and mass E_2 = m_2. The threshold energy E_{1,\text{thr}} to produce three particles of masses m_a, m_b, m_c, i.e.

 1 + 2 \to a + b + c,

is then found by asking these three particles to be at rest in the center of mass frame (symbols with hat indicate quantities in the center of mass frame):

 E_\text{cm} = m_a c^2+ m_b c^2 + m_c c^2 = \hat{E}_1 + \hat{E}_2 = \gamma (E_1 - \beta p_1 c) + \gamma m_2 c^2 .

Here  E_\text{cm} is the total energy available in the center of mass frame.

Using  \gamma = \frac{E_1 + m_2 c^2}{E_\text{cm}} ,  \beta = \frac{p_1 c}{E_1 + m_2 c^2} and p_1^2 c^2 = E_1^2 - m_1^2 c^4 one derives that

E_{1,\text{thr}} = \frac{(m_a c^2+ m_b c^2 + m_c c^2)^2 - m_1^2 c^4 - m_2^2 c^4}{2 m_2 c^2}.

See also[edit]

References[edit]